Probiotic properties of antimicrobial-producing lactic acid bacteria isolated from dairy products and raw milk of Sabah (Northern Borneo), Malaysia - Melisa Elsie Kasimin,; Ainol Azifa Mohd. Faik,; Jaeyres Jani,; Sahar Abbasiliasi,; Arbakariya Ariff,; Roslina Jawan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to evaluate the probiotic properties of the antimicrobial-producing lactic acid bacteria (LAB) isolated from cow and goat milk, and various types of cheese. The isolated strains were biochemically characterized by sequence of tests namely Gram staining, catalase test and carbon fermentation. The agar well diffusion assay was performed by utilizing the Listeria monocytogenes ATCC 7644 and Listeria monocytogenes ATCC 13933 as the indicator microorganisms prior to biochemical and physiological tests to assess the beneficial properties of the strains. Results showed that 5 out of 20 isolated LAB strains were the antimicrobial-producer indicated by the formation of inhibition zones against the L. monocytogenes ATCC 7644 and L. monocytogenes ATCC 13933. All five strains were able to utilize glucose, and also tolerate various concentrations of NaCl and wide range of temperatures. Strains CCB1, GB3 and CB3 showed positive proteolytic activity, while CCB1, GB3 and CA1 were able to hydrolyse starch. Other than that, isolates CCB1, CB3 and CA1 showed ability to deconjugate bile salt in both aerobic and anaerobic conditions. Moreover, CCB1, GB3 and CA4 were susceptible to ampicillin, tetracycline, ceftriaxone, penicillin G and chloramphenicol. However, most of the strains were resistant to norfloxacin, amikacin, colistin sulphate, streptomycin and nalidixic acid. Lastly, all of the five isolates were tolerant to bile salt and phenol as no growth inhibition was observed. The newly isolated LAB strains with valuable features might offer an unfolded potency that are beneficial for applications in food industry.